PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL LEARNING CYCLE 7E KELAS IV SDN 15 ULU GADUT KOTA PADANG - Zikrisyah, Muhammad; Arwin; Anita, Yesi; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study lies in students' unsatisfactory learning achievement in IPAS (Natural and Social Sciences), resulting from teaching practices that had not yet fully embraced a student-centered design and execution. This study sought to portray how applying the 7E Learning Cycle Model could raise pupil performance among fourth graders at SDN 15 Ulu Gadut, located in Padang City. A Classroom Action Research (CAR) design was adopted, blending qualitative and quantitative methods across two cycles, each progressing through the stages of planning, implementation, observation, and reflective evaluation. Involved in the research were the homeroom teacher together with 28 pupils from Class IV.A of SDN 15 Ulu Gadut 15 boys and 13 girls. The data gathered pointed to gains across multiple dimensions: a) the lesson plan quality (RPM) climbed from 80.56% (Fair) during cycle I to 91.67% (Excellent) by cycle II; b) teacher performance grew from 71.87% (Fair) to 90.62% (Good); c) pupil participation likewise rose from 71.87% (Fair) to 90.62% (Good); and d) overall achievement scores advanced from 69.43% (Fair) in the first cycle to 87.68% (Good) in the second. Based on these results, the 7E Learning Cycle Model can be considered an effective approach for raising elementary-level achievement in IPAS subjects.